Lived experiences of first-year radiation therapy students communicating with patients and radiation therapists - A qualitative review using interpretative phenomenological analysis. Issue 1 (February 2022) - Kelly, T.; Thompson, J.D.; Surjan, Y.; Rinks, M.; Warren-Forward, H.
Abstract: Introduction: Radiation therapists must possess adaptable communication skills to manage patient-centred care and provide required technical information. Adaptive communication is also an expectation of undergraduate students to gain registration in Australia. The University Of Newcastle's Clinical Reasoning Module (CRM) prepares first-year radiation therapy students for clinical interactions. This research aims to reveal the lived experience of students after completing their first clinical placement. Methods: An interpretative phenomenological analysis (IPA) approach was the chosen methodology. Audio-recorded semi-structured interviews were conducted with first-year students who had completed the CRM and attended their first placement. Two independent reviewers analysed each data set separately before discussing and agreeing on, and arranging themes into clusters to reveal substantive and sub-themes. Results: Four students were interviewed. Five substantive themes were revealed; 'making sense of the CRM', 'the inner self', ' the art of communication', 'the student as a learner' and 'clinical work'. Students' varied clinical experiences were evident, and the interviews allowed a de-brief mechanism. Students related the CRM to the clinical environment and revealed unexpected reactions and emotional responses during their placement. Examples include disclosing the reluctance of patients to interact and talking about dying, which became their new normal. Conclusion: This review allowed an opportunity to inquire into the lived experiences of radiation therapy students navigating their way through the clinical environment. Differences between student's emotional intelligence and level of communication reflected their ability to make sense of their experiences in the clinical setting. Implications for practice: While students appeared satisfied with the CRM in preparing them for clinical placement, providing regular de-brief sessions and reviewing clinical practice guidelines to better prepare for psycho-social issues encountered is recommended for overall student well-being.